LEFT ATRIAL TO LEFT VENTRICULAR END DIASTOLIC DIAMETER RATIO IN LEFT VENTRICULAR DIASTOLIC DYSFUNCTION - Haq, Inam ul; Saeed, Muhammad; Hamza, Muhammad; Ali, Agha Shabbir; Nadir, Maha (Pakistan Journal of Physiology, 2017)
Background: Diastolic dysfunction (DD) is difficult to diagnose and characterize despite many techniques. It is known that left atrial diameter (LAD) increases and left ventricular internal end diastolic diameter (LVIDD) remains the same in moderate to severe diastolic dysfunction (grade II and above) but a ratio between these two (LAD/LVIDD) has never been used to assess diastolic dysfunction. This study aims to analyze the relationship between the ratio, left atrial diameter/ left ventricular internal end diastolic diameter (LAD/LVIDD) and diastolic dysfunction (grade II and above). This study also aims to give a statistical model based upon this relationship that is able to help in diagnosing diastolic dysfunction. Methods: This case control analytical study was carried out at the Department of Cardiology, Holy Family Hospital, Rawalpindi, from Jan 2014 to Jan 2016. On the basis of echocardiographic findings, 226 patients were identified as normal healthy control group whereas 226 patients were identified as having diastolic dysfunction of grade II and above and were categorised as disease group. Doppler diastolic function parameters were used to assess diastolic function in all of these 452 patients. Appropriate statistical methods were then applied on the data by using IBM statistical package for social sciences (SPSS). Results: LAD/LVIDD was correlated to diastolic dysfunction at r=0.858 (p<0.01). A binary logistic regression model using age, sex and LAD/LVIDD gave an accuracy of 96.9% in diagnosing diastolic dysfunction. LAD/LVIDD in the model had an odds ratio of 2.678Â´1024. A Receiver Operation Characteristic curve between diastolic dysfunction and LAD/LVIDD yielded a specificity of 93.8% and sensitivity of 99.1% at the cut-off value of 0.7268. Conclusion: A new parameter, left atrial diameter (LAD) to left ventricular internal end diastolic diameter (LVIDD) ratio (LAD/LVIDD), is significantly correlated to diastolic dysfunction (grade II and above). It is also a significant predictor for diastolic dysfunction. Pak J Physiol 2017;13(1):15â€“8